2019
DOI: 10.1007/s00441-019-03016-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastric pentadecapeptide body protection compound BPC 157 and its role in accelerating musculoskeletal soft tissue healing

Abstract: There is a current need for a therapy that can alleviate the social and economic burden that presents itself with debilitating and recurring musculoskeletal soft tissue injuries and disorders. Currently, several therapies are emerging and undergoing trials in animal models; these focus on the manipulation and administration of several growth factors implicated with healing. However, limitations include in vivo instability, reliance on biocompatible and robust carriers and restricted application procedures (loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(73 citation statements)
references
References 43 publications
1
72
0
Order By: Relevance
“…We demonstrated that BPC 157 medication [1][2][3][4][5][6][7][8][9][10][11][12][13], given immediately after antithrombotic agents in rats, aspirin, clopidogrel, and cilostazol, counteracted their inhibitory effects on the aggregation activated by the arachidonic acid, ADP, collagen, and arachidonic acid/PGE1 used as aggregation agonists [15][16][17]20]. Contrarily, BPC 157 does not affect Thus, this suggests a particular pleiotropic effect, likely a direct effect, on thrombocyte function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We demonstrated that BPC 157 medication [1][2][3][4][5][6][7][8][9][10][11][12][13], given immediately after antithrombotic agents in rats, aspirin, clopidogrel, and cilostazol, counteracted their inhibitory effects on the aggregation activated by the arachidonic acid, ADP, collagen, and arachidonic acid/PGE1 used as aggregation agonists [15][16][17]20]. Contrarily, BPC 157 does not affect Thus, this suggests a particular pleiotropic effect, likely a direct effect, on thrombocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…Pentadecapeptide Gly-Glu-Pro-Pro-Pro-Gly-Lys-Pro-Ala-Asp-Asp-Ala-Gly-Leu-Val, M.W. 1419, named BPC 157, a part of the sequence of human gastric juice protein, coded BPC, freely soluble in water at pH 7.0 and in saline, was prepared (Diagen, Slovenia) as described previously [1][2][3][4][5][6][7][8][9][10][11][12][13]. L-NAME and L-arginine were commercially purchased (Sigma, USA).…”
Section: Drugs and Protocolmentioning
confidence: 99%
See 3 more Smart Citations